THD Measurement and Simulation of Grid-Connected Solar PV and Wind Integrated Renewable Energy System (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper takes us through different objectives to make the grid-connected hybrid system workeffectively. In this paper, Double-Fed Induction Generator-controlled Wind Energy System integrated with aSolar PV plant is connected to the Grid. The observed non-linear variation of solar irradiation andtemperature was controlled by the MPPT controller which, tries to maintain the maximum power conditionat almost all instants. In this paper, the incremental conductance type MPPT method is employed for solarPV plant whereas, in the case of a wind farm, the use of back-to-back connected VSC incorporated in theDFIG maintains unity power factor for different wind speed variations. As energy availability fromrenewable sources is intermittent, the harmonics at the load side are inevitable. These can was reduced byusing a 3-Level VSC with suitable PWM techniques to some extent. In this paper, three different cases tofind the best way to integrate the wind and solar PV energy systems into the Grid have been considered.MATLAB/SIMULINK was used to do simulations with THD measurements for three different cases.